Design of machine cell in cellular manufacturing systems using PSO approach. (2021) - Adinarayanan, A.; Dinesh, S.; Balaji, DS.; Umanath, K.
Abstract: When the equipments are not located in a systematic manner, part manufacturing using the machineries will be very difficult. Distance travelled by the parts increases which in turn increase the time of production for each product. Hence productivity reduces and the flow of parts will not be smooth. To minimize this problem, Cellular manufacturing (CM) concept is proposed for industries using batch type production. The present work discusses the machine cell formation problem with the objective of minimization of the travelling distance of parts. Time taken by the parts to travel between the machines before and after cell formation is calculated. In this work, various matrix size problems are taken from the literature and tested. One of the meta-heuristic approaches, particle swarm optimization (PSO) algorithm is proposed in this work.